The effects of high intensity interval training on platelet aggregation and phosphorylation of VASPser239 in men with coronary heart disease - Akbar Nouri-habashi; Sajad Ahmadizad; Morteza Salimian; Hiwa Rahmani (فیزیولوژی ورزش و فعالیت بدنی)
Purpose: Exercises increase platelet activation and aggregation in patients with cardiovascular diseases especially at high intensities. The aim of the study was to investigate the effect of 8 weeks of high-intensity interval training on platelet activation and aggregation and phosphorylation of VASPser239 in the coronary heart patients.Methods: For this purpose, twenty CABG and PCI patients (≤ 3 months) participated voluntarily and were randomly divided into two groups; i.e. control (N=10) and interval training (N=10) groups. Anthropometric characteristics and peak oxygen consumption were recorded a week before the start. High-intensity interval training group patients participated in an 8 weeks exercise training program, three times a week. The interval training program consisted of a warm-up, 8 reps/ four min (exercise: 2min, active recovery: 2min, intensity: 90/ 30) and finally, cool down. Each session lasted 40 min. The training intensity was started 75/ 15% of the peak oxygen consumption but gradually increased during the first two weeks to reach 90/ 30% of peak oxygen consumption in the last two weeks. The control group did not participate in regular exercises during this period. Blood samples were taken before and 48h after the last exercise session and analyzed for platelet aggregation, CD62p expression, and phosphorylation of VASPser239. The dependent and independent t-tests were used for statistical analysis.Results: A significant difference was observed between the two groups in the amount of decrease in platelet aggregation and CD62p expression in response to ADP (P <0.05). Also, the VASP phosphorylation at ser239 was increased significantly in response to NO in the interval training group (P<0.05).Conclusion: Eight weeks of high-intensity interval training led to the improvement in platelet activation and aggregation factors in coronary heart patients of this study. It seems that regular high-intensity exercise may improve platelet function, due to a decrease in CD62P expression and an increase in sensitivity to NO production by endothelial cells.